Development of a portable laser-flash photolysis Faraday rotation spectrometer for measuring atmospheric total OH reactivity - B. Fang; N. Wei; W. Zhao; N. Yang; H. Zhou; H. Zhang; H. Zhang; J. Li; W. Zhang; Y. Lu; Y. Lu; Z. Zhu; et al. (Atmospheric Measurement Techniques)
Quantitative measurements of atmospheric total OH reactivity (<msubsup>kOH′</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="3849a30c9dc911b94a681f63125e5695"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-1243-2025-ie00001.svg" width="20pt" height="15pt" src="amt-18-1243-2025-ie00001.png"/></svg:svg>) provide crucial insights into atmospheric photochemistry. However, widespread application of total OH reactivity measurements is challenging due to insufficient equipment and the complexity of existing instrumentation. In this work, we report the development of a portable laser-flash photolysis Faraday rotation spectroscopy (LP-FRS) instrument for real-time and in situ measurement of <msubsup>kOH′</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="552e0d3a2315ba1d60d16278bb83421d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-1243-2025-ie00002.svg" width="20pt" height="15pt" src="amt-18-1243-2025-ie00002.png"/></svg:svg>. To achieve efficient overlapping between the pump and probe laser and realize a long effective absorption path length, thus enabling high-sensitivity measurement, a specific Herriott-type pump–probe optical multi-pass cell was designed. The instrument's optical box dimensions were 130 cm × 40 cm × 35 cm. The obtained effective absorption path was ∼ 28.5 m in a base length of 77.2 cm. The <msubsup>kOH′</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="1e833a76ffad29bbe2689e71e449b546"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-1243-2025-ie00003.svg" width="20pt" height="15pt" src="amt-18-1243-2025-ie00003.png"/></svg:svg> detection precisions of the LP-FRS instrument were 2.3 and 1.0 s−1 with averaging times of 60 and 300 s, respectively. The <msubsup>kOH′</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="a7c6690b6bac039d666646c5b5e9ae58"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-1243-2025-ie00004.svg" width="20pt" height="15pt" src="amt-18-1243-2025-ie00004.png"/></svg:svg> measurement uncertainty was evaluated to be within 2 s−1. Field measurement was performed, and the difference between the measured <msubsup>kOH′</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="781901bd9c68959a83d524b46f5cae82"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-1243-2025-ie00005.svg" width="20pt" height="15pt" src="amt-18-1243-2025-ie00005.png"/></svg:svg> and the model simulated from the measured reactive species was analysed. The developed portable LP-FRS instrument extends the measurement methods of atmospheric total OH reactivity and has certain advantages in terms of cost, operation, and transportation, which will play an increasingly important role in future atmospheric chemistry research.